2016
DOI: 10.1093/mnras/stw662
|View full text |Cite
|
Sign up to set email alerts
|

The mineral clouds on HD 209458b and HD 189733b

Abstract: ABSTRACT3D atmosphere model results are used to comparatively study the kinetic, nonequilibrium cloud formation in the atmospheres of two example planets guided by the giant gas planets HD 209 458b and HD 189 733b. Rather independently of hydrodynamic model differences, our cloud modelling suggests that both planets are covered in mineral clouds throughout the entire modelling domain. Both planets harbour chemically complex clouds that are made of mineral particles that have a height-dependent material composi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 87 publications
(107 reference statements)
4
108
0
Order By: Relevance
“…We chose a hierarchical approach of modelling environments where we utilise 97 1D profiles extracted from the 3D GCM calculated for the cloud-free HAT-P-7b (Mansfield et al 2018) and apply our kinetic cloud formation model consistently linked to an chemical equilibrium code. Our study is the continuation of previous investigations of cloud formation in the giant gas planets HD 189733b and HD 209458b (Lee et al 2015a;Helling et al 2016;Lee et al 2016;Lines et al 2018b), and the super-hot gas giant WASP-18b in order to enable a comparative overview for these two classes of giant gas planets given that observations mainly provide snapshots of certain aspects (e.g. presence of certain gas species, existence of clouds, a hot spot off-set) of each of these planets so far.…”
Section: Introductionsupporting
confidence: 84%
“…We chose a hierarchical approach of modelling environments where we utilise 97 1D profiles extracted from the 3D GCM calculated for the cloud-free HAT-P-7b (Mansfield et al 2018) and apply our kinetic cloud formation model consistently linked to an chemical equilibrium code. Our study is the continuation of previous investigations of cloud formation in the giant gas planets HD 189733b and HD 209458b (Lee et al 2015a;Helling et al 2016;Lee et al 2016;Lines et al 2018b), and the super-hot gas giant WASP-18b in order to enable a comparative overview for these two classes of giant gas planets given that observations mainly provide snapshots of certain aspects (e.g. presence of certain gas species, existence of clouds, a hot spot off-set) of each of these planets so far.…”
Section: Introductionsupporting
confidence: 84%
“…Our results have shown that the super-rotating equatorial jet, found as a solution for hot Jupiter atmospheres from several models (see for example Cooper & Showman 2005;Menou & Rauscher 2009;Rauscher & Menou 2010;Heng et al 2011;Dobbs-Dixon & Agol 2013;Parmentier et al 2013;Showman et al 2015;Helling et al 2016;Kataria et al 2016;Lee et al 2016), is robust in our setup. Our model does not include a drag or friction at the bottom boundary potentially responsible for removing some of the dependence on initial conditions (see Liu & Showman 2013;Cho et al 2015).…”
Section: Resultssupporting
confidence: 59%
“…However, Fe[s] rich grains are expected to reside below the photosphere of HD 189733b (Lee et al 2015;Helling et al 2016a), where they would have negligible effects on the observable scattered and emitted light.…”
Section: Discussionmentioning
confidence: 99%
“…This is converted into a mass opacity by the relation κ sca,H 2 (λ) = n H 2 σ sca,H 2 (λ)/ρ gas . The abundance of molecular H 2 (n H 2 [cm −3 ]) is calculated at each cell assuming chemical equilibrium using the routines from Helling et al (2016a).…”
Section: Cloud and Gas Opacitymentioning
confidence: 99%